2021
DOI: 10.1002/jee.20403
|View full text |Cite
|
Sign up to set email alerts
|

A multiple case study of an interorganizational collaboration: Exploring the first year of an industry partnership focused on middle school engineering education

Abstract: Background Calls to improve learning in science, technology, engineering, and mathematics (STEM), and particularly engineering, present significant challenges for school systems. Partnerships among engineering industry, universities, and school systems to support learning appear promising, but current work is limited in its conclusions because it lacks a strong connection to theoretical work in interorganizational collaboration. Purpose/Hypothesis This study aims to reflect more critically on the process of ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
(82 reference statements)
0
7
0
Order By: Relevance
“…Often, these partnerships result from connections among individuals, specifically teachers reaching out within their network to bridge gaps between student interest and curriculum availability (Hands, 2006). While interpersonal relationships are essential to the success of programs targeting students' vocational success, theories on interorganizational collaboration also emphasize organization-level factors such as hierarchy, shared vision, and resource allocation (Gillen et al, 2021;Badgett, 2016) Researchers have identified that young rural Virginians face issues related to educational attainment such as higher dropout rates, lower graduation rates, and generally lower rates of high school degrees or the equivalent when compared to their peers across the commonwealth in suburban and urban communities (Alleman & Holly, 2012). In rural regions of Virginia, only 27% of the population holds an associate degree or higher, compared to the 51% of the rest of the commonwealth and 46% for the nation (National Center for Education Statistics & U.S. Department of Education, 2017; State Council of Higher Education for Virginia (SCHEV), 2017).…”
Section: Multi-institutional Partnershipsmentioning
confidence: 99%
See 1 more Smart Citation
“…Often, these partnerships result from connections among individuals, specifically teachers reaching out within their network to bridge gaps between student interest and curriculum availability (Hands, 2006). While interpersonal relationships are essential to the success of programs targeting students' vocational success, theories on interorganizational collaboration also emphasize organization-level factors such as hierarchy, shared vision, and resource allocation (Gillen et al, 2021;Badgett, 2016) Researchers have identified that young rural Virginians face issues related to educational attainment such as higher dropout rates, lower graduation rates, and generally lower rates of high school degrees or the equivalent when compared to their peers across the commonwealth in suburban and urban communities (Alleman & Holly, 2012). In rural regions of Virginia, only 27% of the population holds an associate degree or higher, compared to the 51% of the rest of the commonwealth and 46% for the nation (National Center for Education Statistics & U.S. Department of Education, 2017; State Council of Higher Education for Virginia (SCHEV), 2017).…”
Section: Multi-institutional Partnershipsmentioning
confidence: 99%
“…Gillen et al examine the tension in interorganizational collaboration between public-private partnerships, noting factors that can mitigate or amplify the perception of pull between collaboration demands and organizational demands. Gillen et al also identified stressors to collaboration such as organizational culture, beliefs/skill deficits, environment, and available resources (Gillen et al, 2021). COVID-19 exacerbated this tension in STW partnerships.…”
Section: Covid-19 Disruptionsmentioning
confidence: 99%
“…The complex curriculum development environment exemplified by AI education appears to be increasingly common in precollege engineering education (Andrée & Hansson, 2019; Gillen et al, 2021). The planning and development of engineering education policies and programs often goes beyond the public schooling system and is participated in by various external agencies (Olitsky, 2017; Tytler et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, more than half of the studies (56%) integrated science learning into the engineering unit. This was primarily through the use of science concepts to justify design decisions [25] [38]. Table 3 highlights which NGSS core ideas were emphasized during the engineering lesson.…”
Section: Rq3: How Has the Ngss Impacted Learning Goals?mentioning
confidence: 99%
“…Table 3 highlights which NGSS core ideas were emphasized during the engineering lesson. Physical science concepts were dominant, including ideas like energy transfer [38] and forces and motion [16] [21] [22] [36] [44]. For example, students designed a solar oven using ideas of heat transfer [38].…”
Section: Rq3: How Has the Ngss Impacted Learning Goals?mentioning
confidence: 99%